Toward a new concept of "natural balance" in oral estroprogestin contraception. (9th August 2013) - Chabbert-Buffet, Nathalie; Gerris, Jan; Jamin, Christian; Lello, Stefano; Lete, Inaki; Lobo, Paloma; Nappi, Rossella E.; Pintiaux, Axelle
Abstract: The Pill has undergone many changes since its first appearance some 50 years ago. Key developments included the reduction of ethinylestradiol doses and the synthesis of new progestins in order to increase safety, compliance and efficiency. Low-dose combined oral contraceptives (COCs) are currently the preferred option for millions of women. Due to this widespread use, it has been argued that the safety of COCs should be even better, raising the threshold for excellence. Yet in spite of major improvements, there is still an associated risk of venous thromboembolism (VTE). The next step in COCs' evolution should take total estrogenicity and hepatic estro-androgenic balance into account. The focus on the estrogen component – which has not changed in 50 years – has yielded a new class of natural estrogen pills. Following the introduction of a first quadriphasic pill, a monophasic estradiol pill based on the concept of "natural balance" was subsequently made available. These recent achievements could represent a step forward in the evolution of COCs and pave the way for better safety.